2021
DOI: 10.1186/s43014-021-00068-8
|View full text |Cite
|
Sign up to set email alerts
|

Addition of phenolic compounds to bread: antioxidant benefits and impact on food structure and sensory characteristics

Abstract: The use of flours or phenolic extracts obtained from non-traditional sources or agri-food industry by-products has been a strategy used to formulate new bakery products with characteristics of a functional food. However, phenolic compounds present great structural diversity, as well as the ability to interact in a complex way with the macromolecules that constitute the bread matrix. Therefore, the addition of these flours, extracts or pure compounds produces various effects on the microstructure of bread, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…1B), the gluten network was severely disrupted, leading to unacceptable products, which was consistent with the literature reports. 6,10 The sensory evaluation (Table S1 †) considering the specific volume, color (Table S2 †), flavor and taste, and texture also showed a reduced overall acceptance of the TPL-fortified bread.…”
Section: Food and Function Papermentioning
confidence: 99%
See 1 more Smart Citation
“…1B), the gluten network was severely disrupted, leading to unacceptable products, which was consistent with the literature reports. 6,10 The sensory evaluation (Table S1 †) considering the specific volume, color (Table S2 †), flavor and taste, and texture also showed a reduced overall acceptance of the TPL-fortified bread.…”
Section: Food and Function Papermentioning
confidence: 99%
“…Bread is the most common staple food worldwide, and phenolic compound fortification to improve its nutritional value and the antioxidant properties has recently become a hot research area. Indeed, bread supplemented with various phenolic compounds, such as phenolic acids 6 and green tea extracts, 7 has been reported in the literature to improve its health effects, such as antioxidants to prevent some diseases and anti-microbial agents to extend its shelf life. On the other hand, the presence of phenolic compounds also induces negative impacts on the final product quality through various interactions with other food components.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Carotenoids and polyphenols are important plant-based molecules with antioxidant and anti-inflammatory properties. 12 Previously published reviews observed the role of polyphenols and carotenoids in the prevention and treatment of age-related ophthalmic diseases. 13 Among all the carotenoids, lutein (LUT) is the primary one in the human macula, known as the macular pigment.…”
Section: Introductionmentioning
confidence: 99%
“…2. Phenolic compounds can produce a quinone radical via covalent bond formation, and in the presence of oxygen and an alkaline environment, a quinone radical is generated via enzymatic/non-enzymatic reactions (Jongberg et al 2015;Czajkowska-González et al 2021;Zhao et al 2021). In the second step, a quinone forms a dimer via a condensation reaction, known as tannins (which are brown-colored, with a high molecular weight), by reacting with the polypeptide amino acid chain via covalent bonding, and are re-oxidized and react with another polypeptide chain in the third step (Felton et al 1989;Arts et al 2001;Buchner et al 2006).…”
Section: Introductionmentioning
confidence: 99%